Implementasi Model Pembelajaran Competence Based Training (CBT) Berbasis Karakter dalam Praktik Pemesinan Frais - Paryanto Paryanto; Asnawi Asnawi (Department of Mechanical Engineering Education, 2017)
The purpose of this study was to determine the impact of CBT Learning Model based on character in the milling machine practice, in relation with: (1) changes in attitude and behavior of the students, and (2) improvement of students' academic achievement. This research is a classroom action research. The research subjects were the B1 group of 3rd semester students of Mechanical Engineering Education Bachelor Degree program enrolled in Milling Machine Process course. Data were collected by means of observation and tests. Analysis of the data were carried out using quantitative-descriptive techniques. Results of this study are: (1) attitude and behavior of the students were improved with an average of 30.66%, and (2) students' achievement were improved by an average of 17.55%. Tujuan penelitian ini adalah untuk mengetahui dampak penerapan Model Pembelajaran CBT Berbasis Karakter dalam praktik pemesinan frais, yang terkait dengan: (1) perubahan sikap dan perilaku mahasiswa; (2) peningkatan prestasi belajar mahasiswa. Jenis penelitian ini merupakan penelitian tindakan kelas. Subjek penelitian adalah mahasiswa semester 3 Program Studi S1 Pendidikan Teknik Mesin yang mengikuti mata kuliah Proses Pemesinan Frais kelas B1. Pengumpulan data menggunakan teknik observasi dan tes. Analisis data menggunakan teknik deskriptif kuantitatif. Hasil penelitian ini adalah: (1) sikap dan perilaku mahasiswa mengalami peningkatan yaitu rata-rata sebesar 30,66%; (2) prestasi belajar mahasiswa juga mengalami peningkatan rata-rata sebesar 17,55%.